2016
DOI: 10.1111/jvp.12350
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of meloxicam after intravenous, intramuscular and oral administration of a single dose to African grey parrots (Psittacus erithacus)

Abstract: Meloxicam is a nonsteroidal anti-inflammatory drug commonly used in avian species. In this study, the pharmacokinetic parameters for meloxicam were determined following single intravenous (i.v.), intramuscular (i.m.) and oral (p.o.) administrations of the drug (1 mg/kg·b.w.) in adult African grey parrots (Psittacus erithacus; n = 6). Serial plasma samples were collected and meloxicam concentrations were determined using a validated high-performance liquid chromatography assay. A noncompartmental pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
4
25
1
Order By: Relevance
“…In addition, other studies in avian species found that giving meloxicam orally can be associated with slow absorption and poor or variable bioavailability. 2,6,9,10,12 In contrast to the lack of dose effect on T max , t 1/2 , and elimination rate constants, AUC 0-∞ values differed significantly between the 1-and 2-mg/kg doses. With 2 mg/kg meloxicam achieving a C max of 12,239 ng/mL and a t 1/2 of 5.68 h, the target plasma concentration of 3500 ng/mL was maintained for approximately 9.5 h; this duration was considerably longer than the 5.5 h for birds given 1 mg/kg.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, other studies in avian species found that giving meloxicam orally can be associated with slow absorption and poor or variable bioavailability. 2,6,9,10,12 In contrast to the lack of dose effect on T max , t 1/2 , and elimination rate constants, AUC 0-∞ values differed significantly between the 1-and 2-mg/kg doses. With 2 mg/kg meloxicam achieving a C max of 12,239 ng/mL and a t 1/2 of 5.68 h, the target plasma concentration of 3500 ng/mL was maintained for approximately 9.5 h; this duration was considerably longer than the 5.5 h for birds given 1 mg/kg.…”
Section: Discussionmentioning
confidence: 88%
“…Figure 1 depicts the mean plasma concentration of meloxicam at 1 and 2 mg/kg plotted against the 5 time points; the dashed horizontal line shows the plasma concentration (3500 ng/mL) considered to provide analgesia in previous reports regarding various bird species. 2,10,12,14 A noncompartmental model was used to estimate the pharmacokinetic parameters presented in Table 1. Neither T max , t 1/2 , nor elimination rate constants differed significantly between the 2 doses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NSAID meloxicam is, a known selective COX-2 inhibitor (Furst, 1997; Hawkey, 1999; Kimura and Kontani, 2009) that has been shown to cross the blood brain barrier (Dehouck et al, 1992; Novakova et al, 2014). It provides effective pain relief in orthodontic pain and animal models of temporomandibular joint pain without the same risk of adverse side effects (Zarif Najafi et al, 2015; Montesinos et al, 2016; Zhang and Gan, 2017). Although meloxicam administration before a painful nerve root compression has been shown to prevent pain onset (Philips et al, 2017), the pathophysiologic mechanisms responsible its effectiveness after nerve root injury are unknown.…”
Section: Introductionmentioning
confidence: 99%